2015
DOI: 10.4172/2167-0587.1000142
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Leaf Nutrient Remobilization in Coastal Cycas Trees by Tropical Cyclone Damage

Abstract: We studied leaf nutrient status of Cycas nitida leaves that were damaged by Typhoon Haiyan in four contrasting locations in eastern Philippines to determine the influence of tropical cyclone (TC) damage on habitat biogeochemistry. Nitrogen resorption efficiency was below global values, but phosphorus and potassium resorption efficiencies were above global values. Stoichiometric relationships indicated P limitations, and leaf P traits tracked soil P availability. Typhoon Haiyan damage resulted in severe changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 43 publications
(44 reference statements)
2
16
0
Order By: Relevance
“…Plants growing in impoverished soils may exhibit greater disparity of nutrient concentrations along a long leaf rachis. Our results indicate that the plants we sampled were not experiencing nutritional stress, as our data were within or greater than the published range for cycads in general [16][17][18][19][20][21][22][23][24][25] and for this species in particular [8,15,23]. As a minimum, we suggest the soil nutrient status should be measured and reported accurately in future studies [26].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Plants growing in impoverished soils may exhibit greater disparity of nutrient concentrations along a long leaf rachis. Our results indicate that the plants we sampled were not experiencing nutritional stress, as our data were within or greater than the published range for cycads in general [16][17][18][19][20][21][22][23][24][25] and for this species in particular [8,15,23]. As a minimum, we suggest the soil nutrient status should be measured and reported accurately in future studies [26].…”
Section: Discussionsupporting
confidence: 65%
“…One other cycad paper reported the position that was sampled, but the sampling was restricted to leaflets from the middle of the rachis [17]. The majority of cycad publications including leaf tissue analysis results provide no description of location along the rachis where leaflets were sampled [18][19][20][21][22][23][24][25]. Our findings indicate that these past publications without rachis position reported are ambiguous and the methods are not repeatable.…”
Section: Discussionmentioning
confidence: 73%
“…Other papers include soil samples from the experimental sites, but they do not indicate proximity of the samples to the studied cycad plants [44]. We are aware of only two reports that included dedicated soil sampling with descriptions of proximity to the cycad plants that were being studied for green leaf nutrient content [45,46]. Continued research within this agenda must include descriptions of influential soil chemistry, and our results indicate the sampling sites must be constrained within close proximity to the studied cycad plants to enable the legitimacy of the methods.…”
Section: Conservationmentioning
confidence: 99%
“…We argue that there is a need to standardize sampling protocols and conduct more case studies to fully understand what controls leaf nutrient status of cycad species and to compare these traits with other gymnosperm and angiosperm taxa [3]. The sampling protocols have been diverse and the level of detail in sampling methods contrasts among the reports [4][5][6][7][8][9][10][11][12][13][14][15]. We have recently shown that plant size [4] and position of leaflet along the rachis [5] are two plant traits that should be recorded to ensure repeatable methods in cycad leaf nutrient studies.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the plant traits that may influence leaf nutrient concentrations for a range of plants are sun exposure at the leaf level and leaf age. Details on these influential traits are missing from the methods of most published reports on cycad leaf nutrients [7][8][9][10][11][12][13][14][15]. Our objectives were to evaluate the influence of these two plant traits on variation in leaf nutrients for the arborescent Cycas micronesica, a species with a native range that includes Palau, Yap, Guam, and Rota Islands [16].…”
Section: Introductionmentioning
confidence: 99%